The potential for adoption of climate smart agricultural practices in Sub-Saharan livestock systems - García de Jalón, Silvestre; Silvestri, Silvia; Barnes, Andrew P. (Springer, 2016)
Livestock systems play an important role in the livelihoods of many rural communities in Sub-Saharan Africa while being responsible for an important share of human-induced greenhouse gas emissions. This study aimed to evaluate the potential for adoption of climate smart agricultural practices in Sub-Saharan livestock systems, related to the improvement in feed, animal husbandry, and grassland management. These practices present productivity and mitigation benefits and in some cases may also contribute to enhance resilience. In this study, we used a data set of 1538 farm households across nine Sub-Saharan countries. A mixed logit model was used to assess the influence on adoption and to estimate the probability of adoption. Our results show that there seems to be stronger influence of physical and financial capitals on adoption than the other capitals. Different types of capitals influence the uptake of different agricultural practices. Yet the probability of adoption would change across countries. The results of this study could help to refine adoption estimates calculated through global or regional modelling approaches and to inform the design of policies to better target investments in order to foster adoption.
Keywords: Adoption; Climate smart agriculture; Livestock Capitals; Climate change; Mixed logitSub-Saharan Africa